2015
DOI: 10.1371/journal.pone.0136692
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Peptidyl-Prolyl Cis-Trans Isomerase- and Calmodulin-Binding Activity of a Cytosolic Arabidopsis thaliana Cyclophilin AtCyp19-3

Abstract: Cyclophilins, which bind to immunosuppressant cyclosporin A (CsA), are ubiquitous proteins and constitute a multigene family in higher organisms. Several members of this family are reported to catalyze cis-trans isomerisation of the peptidyl-prolyl bond, which is a rate limiting step in protein folding. The physiological role of these proteins in plants, with few exceptions, is still a matter of speculation. Although Arabidopsis genome is predicted to contain 35 cyclophilin genes, biochemical characterization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 73 publications
1
28
0
1
Order By: Relevance
“…ROC2 (CYP19-3): ROC2 physically interacts with calmodulins (CAMs) and thus affects a broad array of reactions controlled by CAMs 48 . These include the response to stress (mediated by the CBL-interacting serine/threonine-protein kinase 6 (SIP3), BTB and TAZ domain protein 4 (BT4) and basic leucine-zipper proteins; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ROC2 (CYP19-3): ROC2 physically interacts with calmodulins (CAMs) and thus affects a broad array of reactions controlled by CAMs 48 . These include the response to stress (mediated by the CBL-interacting serine/threonine-protein kinase 6 (SIP3), BTB and TAZ domain protein 4 (BT4) and basic leucine-zipper proteins; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that besides cis-trans isomerization, members of cyclophilin family also perform additional functions in the cell [5] . We recently demonstrated that an Arabidopsis cyclophilin, AtCyp19-3, which is 72.67% identical to TaCypA-1, interacts with CaM in a Ca 2+ -dependent manner [19] . CaM is one of the most well characterized sensors of Ca 2+ , and it consists of four EF-hands that bind to Ca 2+ cooperatively [20] .…”
Section: Resultsmentioning
confidence: 99%
“…Contingent upon the presence of an extra loop of four or more amino acid residues present at residue 50 corresponding to hCYPA, the cyclophilins are classified as divergent or nondivergent (Dornan et al, 1999). The divergent loop cyclophilins such as TaCYPA-1 (Sekhon et al, 2013), CsCYP (Campos et al, 2013) and Cat r 1 (Ghosh et al, 2014) are similar to hCYPA in their active site composition and CsA binding characteristics except for the presence of a characteristic additional loop (consensus sequence XXGKXLH corresponding to amino acid residues 48-54 in TaCYPA-1), two conserved Cys residues (Cys40 and Cys168) and a conserved glutamate (Glu83) residue (Kaur et al, 2015;Vasudevan et al, 2015). On the contrary, the nondivergent cyclophilins such as hCYPA, SmCYPA and AtCYP20-3 or ROC4 (Rotamase Cyclophilin 4) lack the additional loop and are characterized by two conserved Cys residues at positions 122 and 126 (Gourlay et al, 2007;Laxa et al, 2007).…”
Section: Regulation Of Transcriptionmentioning
confidence: 99%
“…The PPIase activity of cyclophilins, in general, is regulated in a redox-dependent or independent manner. Contrary to the E. coli cyclophilin PPIB, that is regulated by redox-independent mechanisms (Hayano et al, 1991;Kaur et al, 2015), the PPIase activity of AtCYP19-3 (ROC2), AtCYP20-3, SmCYPA, CsCYP and TaCYPA-1 is subject to redox regulation (Motohashi et al, 2003;Gourlay et al, 2007;Laxa et al, 2007;Campos et al, 2013;Kaur et al, 2015Kaur et al, , 2017. Furthermore, the redoxregulatory mechanisms observed in different cyclophilins are also distinct.…”
Section: Regulation Of Transcriptionmentioning
confidence: 99%